Strategic Advertising Management: The Case of the Transportation and Storage Market in the Czech Republic - Gunina, Daria; Bina, Vladislav; Novak, Michal (Communications - Scientific letters of the University of Zilina, 2018)
The aim of this study is to analyse the advertising strategy on the transportation and storage market in the Czech Republic. The study provides information and knowledge of seasonal advertising scheduling by answering three research questions. The statistical analysis is based on a research sample of 840,204 advertisements aired in 2013-2017. The results of the study show different scheduling patterns of subcategories in the transportation and storage market. They also point out that subcategories in the transportation and storage NACE category are different. Therefore, marketing researchers should take this knowledge into account in their generalisations.